2017
DOI: 10.1073/pnas.1616171114
|View full text |Cite
|
Sign up to set email alerts
|

AMPK blocks starvation-inducible transgenerational defects in Caenorhabditis elegans

Abstract: Life history events, such as traumatic stress, illness, or starvation, can influence us through molecular changes that are recorded in a pattern of characteristic chromatin modifications. These modifications are often associated with adaptive adjustments in gene expression that can persist throughout the lifetime of the organism, or even span multiple generations. Although these adaptations may confer some selective advantage, if they are not appropriately regulated they can also be maladaptive in a context-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 60 publications
(60 reference statements)
2
77
0
Order By: Relevance
“…This period of quiescence is referred to as the L1 diapause . Our group and others noted that AMPK is required for the metabolic adjustment that occurs during this starved, developmentally quiescent diapause phase . We also showed that AMPK is required to block epigenetic modifications that ultimately affect the integrity of the germ line, which later has a negative impact on the reproductive capacity of these animals once they develop to the adult stage (Box and Table ).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…This period of quiescence is referred to as the L1 diapause . Our group and others noted that AMPK is required for the metabolic adjustment that occurs during this starved, developmentally quiescent diapause phase . We also showed that AMPK is required to block epigenetic modifications that ultimately affect the integrity of the germ line, which later has a negative impact on the reproductive capacity of these animals once they develop to the adult stage (Box and Table ).…”
Section: Introductionmentioning
confidence: 70%
“…In a recent study, we examined how the AMP activated protein kinase (AMPK), which has been well described for its role in maintaining energy homeostasis in response to several stresses, is also involved in blocking specific chromatin modifications and epigenetic changes in Caenorhabditis elegansCaenorhabditis elegans larvae that are subjected to starvation . In many animals, the disruption of both catalytic subunits, and hence all AMPK signaling, is lethal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 9 mutants defective in stress responses that we examined, only two (daf-16, aak-1/2) did not show altered RNAi inheritance dynamics. Interestingly, daf-16 was shown to be involved in heritable "mortal germline" phenotype (Mrt) (Simon et al, 2018) and aak-1/2 was implicated in regulating transgenerational consequences of starvation (Demoinet et al, 2017). The remaining 7 mutants showed either defective (mek-1/sek-1, kgb-1, hsf-1) or enhanced (pmk-1, sek-1, skn-1, daf-2)…”
Section: Resultsmentioning
confidence: 99%
“…We found that the worms' concentration in liquid affects their size (p<0.0001, One-Way ANOVA), and that while in low concentrations the liquid-grown worms are longer ( Figure 1B and C), in very high concentrations, liquid-grown worms become shorter (perhaps in this condition not enough food is available). As starvation is known to generate heritable effects in C.elegans [8][9][10][11], in all the subsequent experiments we grew worms in liquid in low concentrations (maximum 0.05 worms per microliter, see methods).…”
Section: Progeny Of Liquid-grown Worms Are Longermentioning
confidence: 99%